2014
DOI: 10.3892/ijmm.2014.1658
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin regulates the sestrin 2-AMPK-p38 MAPK signaling pathway and induces apoptosis by increasing the generation of intracellular ROS in a p53-independent manner

Abstract: The induction of apoptosis in cancer cells is a therapeutic strategy for the treatment of cancer. In the present study, we investigated the regulatory mechanisms responsible for quercetin-induced apoptosis, mamely the increased expression of sestrin 2 and the activation of the 5′ AMP-activated protein kinase (AMPK)/p38 MAPK signaling pathway. Our results revealed that quercetin induced apoptosis by generating the production of intracellular reactive oxygen species (ROS) and increasing the expression of sestrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(82 citation statements)
references
References 25 publications
4
68
0
Order By: Relevance
“…Previous studies found that p38 MAPK activation may be regulated by p53 expression and activation via downstream signaling pathways (41,42). Also, the AMPK/p38 MAPK pathway controls apoptosis-related protein expression and induces apoptotic cell death without p53 activation (28). From our results and those of previous studies, we conclude that TJE induces apoptosis and downregulates the mitochondrial outer membrane potential via the AMPK/ p38 MAPK signaling pathway in a p53-indepent manner.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Previous studies found that p38 MAPK activation may be regulated by p53 expression and activation via downstream signaling pathways (41,42). Also, the AMPK/p38 MAPK pathway controls apoptosis-related protein expression and induces apoptotic cell death without p53 activation (28). From our results and those of previous studies, we conclude that TJE induces apoptosis and downregulates the mitochondrial outer membrane potential via the AMPK/ p38 MAPK signaling pathway in a p53-indepent manner.…”
Section: Discussionsupporting
confidence: 77%
“…For this reason, there has been an increased interest in the effect of compounds extracted from natural sources on the prevention and treatment of colorectal cancer. Such compounds induce apoptosis and arrest metastasis through the regulation of intracellular signaling in cancer cells (27)(28)(29)(30)(31)(32)(33). Many researchers have identified food extracts that have been used in cancer chemotherapy experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quercetin exerts its anticancer effects by inducing cell cycle arrest, apoptosis, and differentiation and by suppressing MMP secretion [48]. Moreover, quercetin also reduces tumor cell adhesion, invasiveness, metastasis, and angiogenesis [49, 50]. Therefore, we aspired to evaluate the effects of quercetin on tumor migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Following supernatant aspiration, the cells were washed with PBS twice and then resuspended in 0.5 mL of PBS prior to fluorescent intensity measurements. 31 32 15 µg/mL nystatin, 33 50 µM amiloride, 34 and 10 mg/mL HA. After preincubation for 1 hour, the nanoparticles were added and incubated for a further 2 hours.…”
Section: Flow Cytometrymentioning
confidence: 99%